LC–MS/MS Determination of Ginsenoside Compound K and its Metabolite 20( S )-Protopanaxadiol in Human Plasma and Urine: Applications in a Clinical Study - Yang, Li; Wang, Chun-Yang; Xie, Xiao-Nv; Wang, Yi-Cheng; Peng, Jing-Bo; Huang, Wei-Hua; Chen, Yao; Ouyang, Dong-Sheng; Tan, Zhi-Rong (Bioanalysis, 2019)
Ginsenoside compound K (CK) is considered to be a potential therapeutic drug for rheumatoid arthritis because of its good anti-inflammatory activity. The purpose of this work was to establish a rapid, sensitive and specific method for determination of CK and its active metabolite 20(S)-protopanaxadiol (20(S)-PPD). Materials & methods: The analytes and internal standards were extracted by liquid-liquid extraction. Then, were separated by high performance liquid phase and determined by triple quadrupole mass spectrometry. A LC-MS/MS using liquid-liquid extraction was developed for determining CK over the concentration range 1.00-1002.00 ng/ml and 0.15-54.30 ng/ml for 20(S)-PPD. The lower limits of quantification for CK and 20(S)-PPD were 1.00 and 0.15 ng/ml, respectively. This method was successfully validated for detecting both CK and 20(S)-PPD in the human plasma and urine, and was proved to be suitable for the pharmacokinetic study of CK in healthy Chinese volunteers. ChiCTR-TRC-14004824.